Effects of Co-current and Cross Flows on Circular Enhanced Gravity Plate Separator Efficiencies - Ngu, Lock Hei; Law, P.L; Wong, Kien Kuok (Korean Society of Environmental Engineers, 2014)
This study compares the effects of flow on oil and suspended solids removal efficiencies in circular enhanced gravity plate separator equipped with coalescence medium. Coalescence medium acts to capture rising oil droplets and settling solid particles and assist in the coalescence of oil and coagulation of solid. The circular separator uses an upflow center-feed perforated-pipe distributor as the inlet. The co-current flow is achieved using 4 increasing sizes of frustum, whereas cross flow uses inclined coalescence plates running along the radius of the separator. The different arrangement gave the cross flow separator a higher coalescence plan area per operational volume, minimal and constant travelling distance for the oil droplets and particles, lower retention time, and higher operational flowrate. The cross flow separator exhibited 6.04% and 13.16% higher oil and total suspended solids removal efficiencies as compared to co-current flow.